(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article provides information on some patterns of distribution of humus content in irrigated soils of desert zones. In terms of humus content, irrigated meadow-alluvial soils have a unique character, which is associated with sharp fluctuations in mechanical composition. It also highlights the importance of studying soil organic carbon as an indicator of soil health in the mitigation of climate change consequences. It was established that the studied soils have been provided with low reserves of organic carbon.